Tradition of Malem Songo Marriage in Kedungharjo: Representation of Natural Law Values in the Perspective of Thomas Aquinas - Shodiqin, Mohammad; Maulidiyah, Azzahra Syarafina; Rifqi, Muhammad Jazil (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Malem Songo marriage is a unique tradition that lives in the Tuban community, especially in Kedungharjo. The term Malem Songo refers to the 29th night of Ramadan which is believed to be a night full of blessings. This belief encourages tens to hundreds of couples in the region to hold a marriage contract simultaneously that night. This tradition has been passed down from generation to generation and has become an integral part of the cultural identity of the local community. This research is empirical with a qualitative approach and uses a philosophical framework as an analysis knife. Primary data was obtained through in-depth interviews with the perpetrators, officials of the Widang District KUA, and Kedungharjo community leaders. This article examines the Malem Songo marriage tradition through the perspective of natural law as proposed by Thomas Aquinas. According to Aquinas, the law of nature is a manifestation of the lex aeterna (eternal law of God) which is imprinted in the universal order and guides man to his ultimate existential goal, which is true happiness (beatitudo) in union with the Creator. The findings of the study show that these traditions not only contain deep spiritual values, but also serve as a cultural mechanism to overcome customary constraints, such as weton mismatches. From the perspective of natural law, this tradition reflects the embodiment of lex aeterna and lex naturalis, where human rationality is linked to divine wisdom. Therefore, Malem Songo marriage is not solely seen as a socio-cultural practice, but rather as a concrete representation of universal moral principles such as rationality, justice, and the attainment of true happiness rooted in the theological dimension and eternal moral law.